PALAEOPLEUROCAPSA IN THE RIPHEAN DEPOSITS OF THE NORTH OF THE SIBERIAN CRATON - Goloveenok V.K.; Belova M.Yu. (My University, 1990)
The microfossils of the genus Palasopleurocapsa are characterized by a very distinctive structure. They are the fossilized remains of attached chamesiphonal blue-green algae, in which the thallus is formed of closely adjoining subparallel or upward-fanning cell rows: this distinguishes them from other taxonomic categories and makes them a conspicuous component of the Precambrian microbiotas. It has recently been learned that Palaeoplsurocapsa is extensively developed geographically and is confined to the youngest Precambrian deposits, so that the genus takes on an important biostratigraphic significance.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей